Investigation of Physicochemical Indices and Microbial Communities in Termite Fungus-Combs - Yang, Guiying; Ahmad, Farhan; Zhou, Qihuan; Guo, Meixia; Liang, Shiyou; Gaal, Hassan Ahmed; Mo, Jianchu (Frontiers in Microbiology, 2021)
Termitomyces species are wild edible mushrooms that possess high nutritional value and a wide range of medicinal properties. However, the cultivation of these mushrooms is very difficult because of their symbiotic association with termites. In this study, we aimed to examine the differences in physicochemical indices and microbial communities between combs with basidiomes (CF) and combs without basidiomes (CNF). HPLC, ICP-OES, GC-FID, some commercial kits, high-throughput sequencing of the 16s RNA, and ITS were used. Humidity, pH, and elements i.e., Al, Ba, Fe, Mn, Ni, S, Ca, and Mg were higher while amino acids particularly alanine, tyrosine, and isoleucine were lower in CF as compared to CNF. The average contents of fatty acids were not significantly different between the two comb categories. The bacterial genera Alistipes, Burkholderia, Sediminibacterium, and Thermus were dominant in all combs. Brevibacterium, Brevundimonas, and Sediminibacterium were significantly more abundant in CF. Basidiomycota and Ascomycota were also identified in combs. Termitomyces clypeatus, Termitomyces sp. Group3 and Termitomyces sp. were the most dominant species in combs. However, any single Termitomyces species was abundantly present in an individual comb.